Live : the 50th anniversary tour [compact disc] (Capitol Records, 2013)
2012 marked the 50th anniversary of the Beach Boys. To mark this momentous occasion, the band reunited to tour the country as well as a number of international concerts. This magical tour is now captured on the 41 track collection.